2007
DOI: 10.1093/jac/dkl548
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cefoxitin and moxalactam 30 µg disc diffusion methods for detection of methicillin resistance in coagulase-negative staphylococci

Abstract: Although all DD methods studied here performed well for detecting methicillin resistance in CoNS, moxalactam had a higher accuracy than cefoxitin to differentiate heteroresistant isolates from PBP2a-negative strains. Identification of isolates that should be submitted to a confirmatory test to conclude on methicillin resistance can be easily obtained by combining cefoxitin and moxalactam DD methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
15
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 9 publications
3
15
1
Order By: Relevance
“…One group recommended the use of a combination of oxacillin MIC and moxalactam MIC tests (7); the other recommended the use of a combination of cefoxitin disk and moxalactam disk tests (5). The use of moxalactam tests in combination with cefoxitin and/or oxacillin tests to predict the mecA status of CoNS may deserve further study, given that the use of cefoxitin MICs alone is not optimal for this purpose.…”
mentioning
confidence: 99%
“…One group recommended the use of a combination of oxacillin MIC and moxalactam MIC tests (7); the other recommended the use of a combination of cefoxitin disk and moxalactam disk tests (5). The use of moxalactam tests in combination with cefoxitin and/or oxacillin tests to predict the mecA status of CoNS may deserve further study, given that the use of cefoxitin MICs alone is not optimal for this purpose.…”
mentioning
confidence: 99%
“…The relevance of the moxalactam disk is slightly better for mecA-positive strains, for which Felten et al obtained a better sensitivity compared to that achieved with cefoxitin (97% and 94%, respectively) (3). Moreover, JoinLambert et al demonstrated that the moxalactam disk better differentiated heteroresistant CoNS isolates from mecA-negative isolates (7).…”
mentioning
confidence: 99%
“…Therefore, the cefoxitin disc diffusion method, currently defined as a standard procedure by the European Committee on Antimicrobial Susceptibility Testing (EUCAST) and the Clinical and Laboratory Standards Institute (CLSI), may fail to detect meticillin resistance in these isolates (CLSI, 2016;. The Committee for Antibiotic Susceptibility Testing of the French Society of Microbiology (CA-SFM) introduced a 30 µg moxalactam disc in 2005, which has been proposed to be a better predictor than cefoxitin for the detection of meticillin resistance in CoNS (CA-SFM, 2012;Join-Lambert et al, 2007). We evaluated the effectiveness of various single and combined methods for the detection of meticillin resistance in CoNS, and derived a practical diagnostic approach.…”
mentioning
confidence: 99%